The Dynamic Behaviour of Capacitive Humidity Sensors - J. Majewski (Приборы и методы измерений)
The sensor design features and the sensing material properties which can influence the response time of the polymer-based capacitive humidity sensors are shortly discussed. The ways of specifying the dynamic properties of capacitive humidity sensors in technical data sheets by the leading companies on the market are briefly characterized and discussed.The schematic view and operation of the experimental setup for determining of the dynamic parameters of capacitive humidity sensors at different temperatures of humid air are described. The dynamic behaviour of polymer-based capacitive humidity sensors was registered as the measurement profiles for both positive and negative step changes in humidity level. The response and recovery times, as well as the time constants for the exponential approximation fits of the step responses, were determined either graphically or analytically, based on the collected data.The changes of these parameters under atmospheric pressure within the temperature range from – 30 °C to + 20 °C were analysed. The exemplary transient measurement profiles are shown, together with the illustrations of the graphical method for determining the response and recovery times. Also, the plots of the relationship between response and recovery times as well as time constants, and temperature, are presented. Some explanations of the obtained results are suggested.